Evaluation of a Quality Improvement Intervention to Improve Pediatric Palliative Care Consultation Processes. (December 2021) - Stoyell, Jennifer Forsman; Jordan, Megan; Derouin, Anne; Thompson, Julie; Gall, Sarah; Jooste, Karen R.; Keskinyan, Vahakn Shant; Lakis, Kristen Register; Lee, Yu-Lin Amy; Docherty, Sharron
Background: A critical aspect of pediatric palliative care consultations is the assessment and documentation of patient and family needs. While these assessments usually include a focus on physical pain, there is less standardization of assessments of other physical symptoms and psychosocial, emotional, or spiritual needs. Aims: To improve the breadth of assessment of psychosocial and emotional needs, screen for symptoms other than pain among pediatric patients utilizing palliative care services, and to increase documentation of assessment data from 30%-40% to 80% through practice changes implemented in 2 Plan-Do-Study-Act (PDSA) cycles. Methods: This quality improvement project involved implementing provider education and adapting the palliative care consultation template in the electronic health record to improve breadth and consistency of assessment and documentation during consultations by the interdisciplinary pediatric palliative care team. Two PDSA cycles were performed. Chi squared tests and statistical control charts were used for data analysis. Results: There was statistically significant improvement in the inclusion of documentation of a pediatric palliative care social work note from baseline (32%) to Cycle 2 (57%). Physical symptom screening declined slightly, but not significantly (p = .32) and socio-emotional discussions also declined but not significantly (p = .05). Conclusions: Screening for physical symptoms and discussions with patients and families about psychosocial/emotional needs during the initial palliative care consultations are extremely important in providing effective, holistic, patient-centered care. There is a need for development of pediatric-centric guidelines and quality measures to evaluate pediatric palliative care programs; further research is indicated to determine methods for evaluating compliance with these guidelines.